The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/mrm.28779
|View full text |Cite
|
Sign up to set email alerts
|

A standard system phantom for magnetic resonance imaging

Abstract: Purpose A standard MRI system phantom has been designed and fabricated to assess scanner performance, stability, comparability and assess the accuracy of quantitative relaxation time imaging. The phantom is unique in having traceability to the International System of Units, a high level of precision, and monitoring by a national metrology institute. Here, we describe the phantom design, construction, imaging protocols, and measurement of geometric distortion, resolution, slice profile, signal‐to‐noise ratio (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(89 citation statements)
references
References 28 publications
2
62
0
Order By: Relevance
“…Across all measurements, reported temperature of either the MRI room or of the bulk water in the phantom ranged from 17.1°C to 23.3°C. Previous research demonstrated that the T 1 of NiCl 2 solutions vary by ± 4% over this experimental range [ 20 ]. Therefore, we expect that the variation of T 1 due to temperature is negligible compared to other sources of measurement error (see S1 Fig for additional details).…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Across all measurements, reported temperature of either the MRI room or of the bulk water in the phantom ranged from 17.1°C to 23.3°C. Previous research demonstrated that the T 1 of NiCl 2 solutions vary by ± 4% over this experimental range [ 20 ]. Therefore, we expect that the variation of T 1 due to temperature is negligible compared to other sources of measurement error (see S1 Fig for additional details).…”
Section: Resultsmentioning
confidence: 93%
“…The focus of this study was the NiCl 2 array (previously called the T 1 array) in the ISMRM/NIST system phantom. The NiCl 2 array was chosen since it has a smaller temperature and field dependence than other available reference arrays [ 20 ]. The NiCl 2 array contains 14 spheres that are doped with varying concentrations of NiCl 2 to achieve a progression of T 1 values from approximately 20 ms to 2000 ms at 1.5 T. The reference T 1 times at 1.5 T and 3 T were determined using the NMR-based relaxation time measurement service provided by NIST.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations